Dampak Perilaku Manajemen Keuangan Pada Pelaku UMKM Ekonomi Kreatif Sub Sektor Kuliner Sate Bandeng Di Kecamatan Serang Kota Serang Banten - Fikri Faisal; Hamdan Hamdan; Deni Sunaryo (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study sought to ascertain the effects of financial management practices on Micro, Small and Medium Enterprises in the Sate Bandeng culinary sub-sector's creative economy in Serang District, Serang City. Using 30 informants, a descriptive qualitative approach was used for this study's research design. Observation, reading, interviews, and documentation studies are all used as data collection methods. techniques for data analysis that include gathering data, reducing it, presenting it, and drawing conclusions. The study's findings indicate that the Sate Bandeng culinary economy's Micro, Small, and Medium Enterprises are impacted by financial management practices. This can be seen from the perspective of financial literacy, record keeping, investments, and savings that can have a pretty significant impact on income for Micro, Small, and Medium Enterprise actors in the creative economy of the milkfish satay culinary sub-sector in Serang District, Serang City, before, during, and after the Covid-19 pandemic. Future studies are anticipated to look at the advantages of technical financial advice in order to advance knowledge and skills in financial management and reveal how awareness of financial management's significance is one of the keys to raising the standard of business in the future.